The types of hepatic myofibroblasts contributing to liver fibrosis of different etiologies - Xu, Jun; Liu, Xiao; Koyama, Yukinori; Wang, Ping; Lan, Tian; Kim, In-Gyu; Kim, In H.; Ma, Hsiao-Yen; Kisseleva, Tatiana (Frontiers in Pharmacology, 2014)
Liver fibrosis results from dysregulation of normal wound healing, inflammation, activation of myofibroblasts and deposition of extracellular matrix (ECM). Chronic liver injury causes death of hepatocytes and formation of apoptotic bodies, which in turn, release factors that recruit inflammatory cells (neutrophils, monocytes, macrophages, and lymphocytes) to the injured liver. Hepatic macrophages (Kupffer cells) produce TGF1 and other inflammatory cytokines that activate Collagen Type I producing myofibroblasts, which are not present in the normal liver. Secretion of TGF1 and activation of myofibroblasts play a critical role in the pathogenesis of liver fibrosis of different etiologies. Although the composition of fibrogenic myofibroblasts varies dependent on etiology of liver injury, liver resident Hepatic Stellate Cells (HSCs) and Portal Fibroblasts (PFs) are the major source of myofibroblasts in fibrotic liver in both experimental models of liver fibrosis and in patients with liver disease. Several studies have demonstrated that hepatic fibrosis can reverse upon cessation of liver injury. Regression of liver fibrosis is accompanied by the disappearance of fibrogenic myofibroblasts followed by resorption of the fibrous scar. Myofibroblasts either apoptose or inactivate into a quiescent-like state (e.g. stop collagen production and partially restore expression of lypogenic genes). Resolution of liver fibrosis is associated with recruitment of macrophages that secrete matrix-degrading enzymes (matrix metalloproteinase, collagenases) and are responsible for fibrosis resolution. However, prolonged/repeated liver injury may cause irreversible crosslinking of ECM and formation of uncleavable collagen fibers. Advanced fibrosis progresses to cirrhosis and hepatocellular carcinoma (HCC). The current review will summarize the role and contribution of different cell types to populations of fibrogenic myofibroblasts in fibrotic liver.